2013
DOI: 10.1371/journal.pone.0069851
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 1 Expression and Its Polymorphic Variants Associate with Breast Cancer Phenotypes

Abstract: Several epidemiological studies have suggested a link between melanoma and breast cancer. Metabotropic glutamate receptor 1 (GRM1), which is involved in many cellular processes including proliferation and differentiation, has been implicated in melanomagenesis, with ectopic expression of GRM1 causing malignant transformation of melanocytes. This study was undertaken to evaluate GRM1 expression and polymorphic variants in GRM1 for associations with breast cancer phenotypes. Three single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 59 publications
3
37
0
1
Order By: Relevance
“…We reasoned that glutamate might act through a glutamate receptor, such as metabotropic glutamate receptor 1 (GRM1), which is expressed by some breast cancers (Mehta et al, 2013; Speyer et al, 2012). However, HIF1α induction by glutamate in TNBC lines was not blocked by glutamate receptor antagonists such as the GRM1 antagonists, BAY 36-7620 and JNJ 16259685; or the GRM2/3 antagonist, LY 341495 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reasoned that glutamate might act through a glutamate receptor, such as metabotropic glutamate receptor 1 (GRM1), which is expressed by some breast cancers (Mehta et al, 2013; Speyer et al, 2012). However, HIF1α induction by glutamate in TNBC lines was not blocked by glutamate receptor antagonists such as the GRM1 antagonists, BAY 36-7620 and JNJ 16259685; or the GRM2/3 antagonist, LY 341495 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Glutamate can also alter cancer cell behavior by modulating ionotropic glutamate receptors, such as the AMPA receptor and NMDA receptors, and metabotropic glutamate receptors (Stepulak et al, 2014; Willard and Koochekpour, 2013). Indeed, a role for the NMDA receptor and metabotropic glutamate receptor-1 in breast cancer has been previously suggested (Mehta et al, 2013; North et al, 2010; Speyer et al, 2012). Secretion of glutamate by glioblastoma cells promotes invasion and tumorigenesis at least partly by causing neuroexcitatory death of surrounding normal brain cells and by activating AMPA receptors (Stepulak et al, 2014; Willard and Koochekpour, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study using 1000 breast cancer patients showed association of this SNP in ER+/PR+ ductal carcinoma in TT-genotype carrier with later age at diagnosis (4.9 years) as compared to either TC- and CC-genotype carriers [32]. However, no association was found with melanoma susceptibility [33].…”
Section: Discussionmentioning
confidence: 90%
“…In particular, mGluRs have been shown empirically to be the predominant mediators of glutamatergic signaling in many cancers (Khan et al, 2011; Koochekpour, 2013; Martino et al, 2013; Speyer et al, 2014; Teh and Chen, 2012; Zhang et al, 2015). The mechanisms by which mGluRs modulate peripheral cell transformation and tumor growth are postulated to be either ectopic expression of wild type mGluRs, increased proliferative signals arising from receptor overexpression, mutations, or expression of polymorphic variants (Ali et al, 2014; Brocke et al, 2010; Mehta et al, 2013; Namkoong et al, 2007; Wall et al, 2014; Zhang et al, 2015). …”
Section: Mglurs In Cancermentioning
confidence: 99%
“…While the contributions of mGluR1 overexpression in breast cancer were explored, a correlation between the polymorphic variants of GRM1 and breast cancer subtypes was demonstrated (Mehta et al, 2013). Earlier, in a genetic association study examining correlation of 3 single nucleotide polymorphisms in GRM1 and melanoma susceptibility showed higher frequency of one of the polymorphisms in GRM1-positive melanoma patients compared to controls.…”
Section: Mglur1 In Breast Cancermentioning
confidence: 99%